Tectono‐thermal Evolution of a Distal Rifted Margin: Constraints From the Calizzano Massif (Prepiedmont‐Briançonnais Domain, Ligurian Alps). Issue 12 (22nd December 2017) - Decarlis, Alessandro; Fellin, Maria Giuditta; Maino, Matteo; Ferrando, Simona; Manatschal, Gianreto; Gaggero, Laura; Seno, Silvio; Stuart, Finlay M.; Beltrando, Marco
Abstract: The thermal evolution of distal domains along rifted margins is at present poorly constrained. In this study, we show that a thermal pulse, most likely triggered by lithospheric thinning and asthenospheric rise, is recorded at upper crustal levels and may also influence the diagenetic processes in the overlying sediments, thus representing a critical aspect for the evaluation of hydrocarbon systems. The thermal history of a distal sector of the Alpine Tethys rifted margin preserved in the Ligurian Alps (Case Tuberto‐Calizzano unit) is investigated with thermochronological methods and petrologic observations. The studied unit is composed of a polymetamorphic basement and a sedimentary cover, providing a complete section through the prerift, synrift, and postrift system. Zircon fission track analyses on basement rocks samples suggest that temperatures exceeding ~240 ± 25°C were reached before ~150–160 Ma (Upper Jurassic) at few kilometer depth. Neoformation of green biotite, stable at temperatures of ~350 to 450°C, was synkinematic with this event. The tectonic setting of the studied unit suggests that the heating‐cooling cycle took place during the formation of the distal rifted margin and terminated during Late Jurassic (150–160 Ma). Major crustal and lithospheric thinning likely promoted high geothermal gradients (~60–90°C/km) and triggered the circulation of hot, deep‐seated fluids along brittle faults, causing the observed thermal anomaly. Our results suggest that rifting can generate thermal perturbations at relatively high temperatures (between ~240 and 450°C) at less than 3 km depth in the distal domains during major crustal thinning preceding breakup and onset of seafloor spreading. Key Points: Distal rifted margins of magma‐poor systems suffer a synrift thermal pulse The thermal anomaly at distal rifted margin also affects shallow crustal levels with relatively high temperatures of up to 350–450° The thermal anomaly is vehiculated toward the upper crust by hydrothermal activity concentrated along distal margin normal faults